Motivasi sebagai Faktor Pendorong Kepatuhan Pengobatan pada Pasien Tuberkulosis. - Rizqiyana, Fika; Widiya Nurhikmah; Desi Sri Rejeki (Journal Pharma Saintika, 2025)
Tuberculosis (TB) remains a major public health concern that requires long-term treatment with Anti-Tuberculosis Drugs (ATDs). The success of therapy largely depends on patient’s adherence to the prescribed regimen, which is influenced by various behavioral and psychosocial factors. This study aimed to determine the level of medication adherence among TB patients taking ATDs and analyze the factors influencing adherence, including knowledge, motivation, and social support. A descriptive quantitative study with a cross-sectional was conducted involving 43 respondents selected through total sampling. Data were collected using the Morisky Medication Adherence Scale 8 (MMAS-8) and questionnaires assessing knowledge, motivation, and social support. The findings showed that 41,9% patients had low adherence, 25,6% had moderate adherence, and 32,6% had high adherence. Of the three factors analyzed, ony motivation exhibited a statistically significant association with adherence (p= 0,038), while knowledge (p=0,757) and social support (p=0,216) did not show significant associations. In conclusion, motivation represents a major determinant of adherence among TB patients. Interventions that emphasize motivational enhancement and educational engangement by healthcare providers should be prioritized to improve adherence and optimize treatment outcomes for tuberculosis.